Mapping and nutrient enrichment studies of seagrass beds in Sepanggar Bay, Sabah - Marjorie, Albert Chagat (Universiti Malaysia Sarawak (UNIMAS), 2005)
(Remotely sensed images from SPOT-4 satellite were used to map the distribution of seagrass habitat in Sepanggar Bay, Sabah. Ground truthing was carried out at the study sites to determine the actual underwater features and then compared to those in the images. Five major cover types were identified during the survey, namely seagrass, seaweeds, mix seagrass and seaweeds, live and dead corals and bare sand. Seven species of seagrasses were found including Enhalus acoroides, Cymodocea serrulata, C. rotundata, Halophila ovalis, Thalassia hemprichii, Halodule uninervis and Syringodium lsoetifollum. Digital image processing software (Integrated Land and Water Information System, ILWIS) was applied to the images for the development of seagrass thematic maps using a supervised classification procedure. ) The overall maps accuracies for North Sepanggar Bay, Sepanggar Island and South Sepanggar Bay were 63.5 %, 56.3 % and 59.2 %, respectively. Despite the low accuracy, the present baseline seagrass maps are still useful for conservation and management plan of the area. Along with mappings, nutrient enrichment studies were also conducted to determine the nutrient status of the seagrass in the bay. Enhalus acoroides at South Sepanggar Bay and Cymodocea serrulata at Sepanggar Island were enriched with two loads of timereleased fertilizer; high load (+NPK; 70.4 gm-2) and low load (+NPK; 35.2 gm-2). After 3 months of fertilization, tissue nitrogen concentrations in aboveground and belowground parts of the E. acoroides were significantly increased in response to both the low and high loads of fertilizers. However, the aboveground tissues of C. serrulata did not exhibit significant results in response to low load fertilization. Other parameters, chlorophyll production, shoot growth rates and biomass was not significantly increased during the three months enrichment period. Hence, tissue nitrogen content is the appropriate parameter for short study using time-released fertilizer. Concentrations of ammonium and phosphate in the sediment pore water and water column were also increased. At the end of the nutrient additions ammonium concentrations in pore water and water column at Station 1 (Sepanggar Island) were found increased with concentrations in the fertilized plots ranged from 0.006 - 0.008 μM and 0.004 - 0.006 μM in the control plots in response to both high and low load fertilizations. However, the concentrations of phosphate in sediment pore water and water column in fertilized plots (0.003 - 0.004 μM) were comparable to that of the controls (0.004 . tM), both under high and low load enrichments. At Station 2 (South Sepanggar), results indicated that concentrations of ammonium and phosphate increased in the fertilized plots (ranging from 0.008 to 0.018 pM and 0.005 to 0.011 pM respectively) at the end of the enrichment experiments as compared to those in the control plots (ammonium 0.003 - 0.011 pM and phosphate 0.001 - 0.006 μM).